2023
DOI: 10.3389/fpsyg.2023.1084836
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological capital and work engagement of kindergarten teachers: A latent profile analysis

Abstract: Although the importance of psychological capital has been firmly supported by prior studies, the question of whether certain subgroups exist and how these various subgroups affect work engagement differentially remains under-explored. To gain an in-depth understanding of this problem, the present study conducted a person-centered method (latent profile analysis) to identify subgroups and then explore the relationship between psychological capital subgroups and work engagement. The study participants were kinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…In the context of Chinese preschool education, work engagement embodies a motivational state that not only has a consequential impact on students’ outcomes, but also on personal wellbeing and institutional objectives. In China, where the educational landscape is rapidly evolving, the well-being of preschool teachers has garnered increased attention ( Gao et al, 2023 ). This shift in focus is not merely about enhancing job satisfaction but also about recognizing teachers as workers whose personal well-being is linked to their professional efficacy and, by extension, to the developmental outcomes of their students.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In the context of Chinese preschool education, work engagement embodies a motivational state that not only has a consequential impact on students’ outcomes, but also on personal wellbeing and institutional objectives. In China, where the educational landscape is rapidly evolving, the well-being of preschool teachers has garnered increased attention ( Gao et al, 2023 ). This shift in focus is not merely about enhancing job satisfaction but also about recognizing teachers as workers whose personal well-being is linked to their professional efficacy and, by extension, to the developmental outcomes of their students.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Psychological capital is a positive psychological state encompassing personal resources such as hope, efficacy, resilience, and optimism ( Luthans et al, 2007 ), forming the acronym HERO. Research has consistently shown its significant benefits for work-related outcomes, including performance, productivity ( Peterson et al, 2011 ; Baykal and Zehir, 2018 ), engagement ( Gao et al, 2023 ), innovative behavior ( Karakitapoğlu-Aygün et al, 2020 ; Özsungur, 2020 ; Li et al, 2021 ), and well-being ( Luthans et al, 2013 ; Youssef-Morgan and Luthans, 2015 ). Employees with higher PsyCap levels tend to exhibit be more satisfied, committed, relaxed ( Avey et al, 2010 , 2011b ; Luthans and Youssef-Morgan, 2017 ) and openness to change ( Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%